Examination of Catalase enzyme in fresh leaves and study some chracters of it (مجلة ديالى للبحوث الانسانية, 2022)
CATALASEIEC: 1 .1 1.1.6) was eliminated in the lettuce Lactuca sativa ,cabbage Brassia oleracea, spinach Spiacia olearacea, Chard Beta vulgarer leaves , enzyme assay ,protein contains , optimum temperature of .Activity & stability ,optimum ph of activity & stability .The result shower The chard Beta bulgaria leaves was biggest activity of database enzyme was (256.897) U/mg , protein contain was ( 4.797) mg/mi , optimum temperature of activity 50c was(0.256) U/ml , optimum temperature of stability 50C to chelation 30 min , CAT has optimum ph of activity 8 was (0.608) U/ml , optimum ph of stability was (1.455)U/ml